Let's say you're given the following problem in vertex form: Y = 2(x + 1)^2 - 8

When converting this to factored form, you will first need to convert it to standard form (which is y = Ax^2 + Bx + C) and then from standard form, convert it to factored form.

y = 2(x^2 + 2x + 1) - 8 Factor out the (x + 1)^2

y = 2x^2 + 4x + 2 - 8 Distribute the 2 to every term in the parenthesis.

y = 2x^2 + 4x - 6 Combine like terms. This is in standard form, and we are now ready to factor this equation to get it into factored form.

y = 2(x^2 + 2x - 3)

**y = 2(x + 3)(x - 1)** <- This is in factored form.